The impact of age and gender on the ICF-based assessment of chronic low back pain. Issue 10 (8th May 2019) - Fehrmann, Elisabeth; Kotulla, Simone; Fischer, Linda; Kienbacher, Thomas; Tuechler, Kerstin; Mair, Patrick; Ebenbichler, Gerold; Paul, Birgit
Abstract: Purpose: To evaluate the impact of age and gender on the international classification of functioning, disability and health (ICF)-based assessment for chronic low back pain. Methods: Two hundred forty-four chronic low back pain patients (52% female) with a mean age of 49 years (SD =17.64) were interviewed with the comprehensive ICF core set for activities and participation, and environmental factors . After conducting explorative factor analysis, the impact of age and gender on the different factors was analyzed using analyzes of variances. Results: Results revealed that older patients experienced more limitations within "self-care and mobility" and "walking" but less problems with "transportation" compared to younger patients. Older or middle-aged low back pain patients further perceived more facilitation through "architecture and products for communication", "health services", and "social services and products for mobility" than younger patients. Regarding gender differences, women reported more restriction in "housework" than men. An interaction effect between age and gender was found for "social activities and recreation" with young male patients reporting the highest impairment. Conclusions: The study demonstrated that the comprehensive ICF core set classification for chronic low back pain is influenced by age and gender. This impact is relevant for ICF-based assessments in clinical practice, and should be considered in intervention planning for rehabilitative programs. Implications for rehabilitation: It is important to consider age and gender differences when classifying with the ICF. The intervention planning based on the ICF should focus on improvement of bodily functioning and mobility in older patients, facilitation of household activities in women, consideration of work-life balance and recreation (e.g., through mindfulness based stress reduction), and reduction of dissatisfaction with rehabilitation in younger patients. It is important to offer patients the opportunity to participate in intervention planning based on the ICF. For intervention planning professionals should bear in mind the resource-oriented approach of the ICF (e.g., facilitation through environmental factors), and a collaboration with other professionals.